2013
DOI: 10.1016/j.eats.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Surgical Technique for Subpectoral Biceps Tenodesis Using a Double-Loaded Suture Anchor

Abstract: Multiple different surgical techniques have previously been described to address long head of the biceps tendinopathy. Subpectoral biceps tenodesis has proven to be an effective procedure to relieve pain and maintain function. We describe a surgical technique for subpectoral biceps tenodesis using a single double-loaded suture anchor implant. Advantages of this procedure include the ease of implant placement and the freedom this technique affords to perform the anchor placement without direct visualization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…1,2 Various techniques, both arthroscopic and open, have been described concerning fixation options and proximal (upper portion of the groove) or distal ("suprapectoral" or "subpectoral") tenodesis location. [3][4][5] Specifically, it has been advocated that proximal tendon fixation is related to persistent postoperative bicipital pain. This is possibly due to the inflammation of the remaining tendon within the groove.…”
mentioning
confidence: 99%
“…1,2 Various techniques, both arthroscopic and open, have been described concerning fixation options and proximal (upper portion of the groove) or distal ("suprapectoral" or "subpectoral") tenodesis location. [3][4][5] Specifically, it has been advocated that proximal tendon fixation is related to persistent postoperative bicipital pain. This is possibly due to the inflammation of the remaining tendon within the groove.…”
mentioning
confidence: 99%
“…Alternatively, many surgeons favor an open subpectoral technique for biceps tenodesis using an interference screw [61], suture anchor [62], unicortical button [63], or bicortical button for fixation [64]. A recent study by Green et al demonstrated good results in a technique that involves docking the tendon into a socket in the humerus without the use of an interference screw [65].…”
Section: Biceps Tenodesismentioning
confidence: 99%
“…Tenodesis is a tenotomy, and a reinsertion of the tendon either in the intertubercular sulcus or in the subpectoral part of humerus by the use of interference-screws (5) and anchors (6). Because of the need of surgical dissection, the use of Homan retractors, drill-holes, interference-screws and anchors, there is a risk of postoperative pain, infection and nerve-lesion (4,7) after this type of surgery, however most studies report a low rate of complications and good functional outcome after these procedures (1,2,3).…”
Section: Introductionmentioning
confidence: 99%